(untitled) (Baghdad Science Journal, 2015)
The present work involved two steps: the first step include Mannich reaction was carried out on 2- mercaptobenzimidazole using formaldehyde and different secondary amine or amide to gives the compounds(2-16). The secnd step include preparation of (Ethylbenzimidazoly-2-mercaptoacetate)(17) from the reaction of 2- mercaptobenzimidazole with ethylchloroacetate than prepared hydrazide derivative[18]from reaction of compound(17) with hydrazinehydrate. Followed Preparation of shiff bases(19-24) and there reaction with mercaptoacetic acid to give a new compounds containing thiazolidinderivetives(25-30).Structure confirmation of all prepared compound were proved using FTIR and element analysis (C.H.N.S) and mesurmentedmelting point.